Laparoscopic Repair of Perforated Peptic Ulcer: Outcome and Associated Morbidity and Mortality - Mahdi Alemrajabi; Saeed Safari; Adnan Tizmaghz; Fatemeh Alemrajabi; Ghazaal Shabestanipour (Electronic Physician, 2016)
Introduction: The mainstay of treatment for perforated peptic ulcer is Omental patch closure. With the advent of laparoscopic surgery, this approach is being used for the treatment of perforated peptic ulcer. The aim of this study was to evaluate the outcome of laparoscopy in Firoozgar general hospital over a period of 18 months. The outcome of the laparoscopic approach and the associated morbidity and mortality, operation time, conversion rate and hospital stay were assessed. Methods: A prospective analysis of 29 consecutive patients (mean age 37.5 years; 23 men) with perforated peptic ulcers and who had undergone laparoscopic surgery was carried over a period of 18 months from March 2014 until September 2015. Pre-operative, intra-operative, and post-operative clinical data were collectively analyzed by SPSS 19 for Windows. Results: Seventeen patients had a history of cigarette smoking, 11 patients had a history of opium consumption, 19 were chronic NSAID users, 26 had Helicobacter pylori infections, and six had a co-morbid condition. Previous surgical history included laparotomy for pancreatic cancer in two patients, for sigmoid colon cancer in one patient, and for acute appendicitis in four patients. The average operating time for all cases was 47.5 + 20 min. The mean lag time between onset of symptoms and surgery was 20.4 hours. All patients underwent laparoscopic closure of the perforation with Omental patch closure. No morbidity was observed, and none of the patients needed conversion to open surgery. One patient died after 11 months of follow-up due to the progression of underlying pancreatic cancer. The mean postoperative hospital stay was 4.2 days. Conclusions: The results of the laparoscopic approach for perforated peptic ulcer were promising, with no conversion to open surgery, no morbidity, and mortality